1992
DOI: 10.1002/crat.2170270806
|View full text |Cite
|
Sign up to set email alerts
|

Control of Nucleation in Gel by GNGT — I

Abstract: The graded neutral gel technique (GNGT) was evolved to control the nucleation in the gel growth of crystals. It was executed in stages using simple devices. Tartrate crystals of five different types were grown under excellent control of nucleation. Crystals of increased size and excellent perfection were produced by this method. Habit modification was found to take place in certain cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Figure 1 shows a KDP crystal grown in gel under completely controlled nucleation by GNGT. Twinned crystals of ADP were found grown exactly below the tip of the cavity in the graded neutral gel, in one of our experiments as found earlier in our gel growth of potassium hydrogen tartrate crystals by GNGT ( SIVANESAN et al 1992). Ammonium sulphate crystallizes in gel with three different types of morphologies in the different regions of the gel column.…”
Section: Methodsmentioning
confidence: 67%
See 1 more Smart Citation
“…Figure 1 shows a KDP crystal grown in gel under completely controlled nucleation by GNGT. Twinned crystals of ADP were found grown exactly below the tip of the cavity in the graded neutral gel, in one of our experiments as found earlier in our gel growth of potassium hydrogen tartrate crystals by GNGT ( SIVANESAN et al 1992). Ammonium sulphate crystallizes in gel with three different types of morphologies in the different regions of the gel column.…”
Section: Methodsmentioning
confidence: 67%
“…The graded neutral gel technique evolved in our research work (SIVANESAN et al 1992 and applied initially to the gel growth of crystals by chemical reaction method proved to be a simple but successful and competent method in controlling the excessive nucleation besides fulfilling the long cherished ambition of the crystal grower, namely crystal growth at the predetermined space (HENISCH). Extension of the application of GNGT to the growth of potassium dihydrogen ortho-phosphate (KDP), ammonium dihydrogen ortho-phosphate (ADP), ammonium sulphate, potassium nitrate, triglycine sulphate (TGS), and ferric alum crystals by solubility reduction process reiterate, confirm the results observed earlier.…”
Section: Introductionmentioning
confidence: 99%
“…For the growth of calcium tartrate crystals it is customary to diffuse calcium chloride solution into the gel charged with tartaric acid. It has been reported that (Sivanesan et al 1992;Henisch 1996) the size of calcium tartrate crystals growing in the gel did not improve even after applying nucleation control techniques like concentration programming and neutral gel methods.…”
Section: Introductionmentioning
confidence: 99%